Atomistic modelling of the diffusion of C in FeCr alloys. (15th February 2019) - Herschberg, Rafael; Fu, Chu-Chun; Nastar, Maylise; Soisson, Frédéric
Abstract: The diffusion of C in FeCr solid solutions is modelled and compared to experimental data. A set of binding energies and migration barriers for C diffusion in different local chemical environments are first calculated using density functional theory. A pair interaction model is developed in order to reproduce these data and predict the migration barriers in other environments. The diffusion model is then implemented in a kinetic Monte Carlo method to simulate tracer diffusion experiments, using a standard procedure, and internal friction experiments, using a novel method. Simulations of internal friction show a unique Snoek peak in the whole concentration range, between pure iron and pure chromium. The average migration barrier for C diffusion in FeCr alloys is found to increase progressively with the Cr concentration, with a small rate below 6 %Cr. In Cr-rich alloys, the effective migration barrier for C diffusion is found to be larger in tracer diffusion than in the internal friction simulations. We conclude that the effective migration barrier extracted from tracer diffusion is closely related to trapping effects of C atoms in Fe-rich local environments, whereas the migration barrier associated with internal friction is mainly controlled by the migration barriers of the most probable configurations, as it is clearly shown in the Cr-rich domain. Graphical abstract: Tracer diffusion and Internal Friction experiments were simulated via AKMC and compared with the available experimental data. A new model for the Internal Friction was developed and it was also compared with a previous model found in the experimental literature. Image 1